Comparison of Campylobacter populations isolated from a free-range broiler flock before and after slaughter. - Colles, F; McCarthy, N; Sheppard, S; Layton, R; Maiden, M (2010)
Relatively little is known about the Campylobacter genotypes colonizing extensively reared broiler flocks and their survival through the slaughter process, despite the increasing demand for free-range and organic products by the consumer. Campylobacter isolates from a free-range boiler flock, sampled before and after slaughter, were genotyped by MLST (multilocus sequence typing) and sequence analysis of the flaA short variable region (SVR). The Campylobacter genotypes isolated before and after slaughter were diverse, with up to five sequence types (STs) (seven-locus allelic profiles resulting from MLST) identified per live bird, up to eight STs identified per carcass and 31 STs identified in all. The majority (72.0%) of isolates sampled from carcasses post-slaughter were indistinguishable from those isolated from the live flock before slaughter by ST and flaA SVR type, however, sampling 'on-farm' failed to capture all of the diversity seen post-slaughter. There were statistically significant increases in the genetic diversity of Campylobacter (p=0.005) and the proportion of C. coli (p=0.002), with some evidence for differential survival of genotypes contaminating the end product. C. coli genotypes isolated after slaughter were more similar to those from free-range and organic meat products sampled nationally, than from the live flock sampled previously. This study demonstrated the utility of MLST in detecting genetic diversity before and after the slaughter process.